The Relationship Between Quality Factors and Online Education Satisfaction: The Moderating Role of Communication Quality in Shanghai, China - Fei, Hu; Tahir, Suhaidah Binti (South Asian Journal of Social Sciences and Humanities, 2024)
Purpose: The rapid advancement and technology have turned every page of life and have primarily affected the student life and education domain. Since COVID pandemic, the education sector embraced the online medium and tried its best effort to effectively continue the learning stream and to evaluate the student satisfaction with the online education system, this study developed an empirical model framing the impact of interactivity, course availability and learning style on the student satisfaction with the catalytic role of cognitive engagement and the external role of communication quality. Method: The study was conducted in the education sector and students who use online platforms and learning materials were targeted within the boundaries of China and the sample size was decided according to item response theory i.e., 440. The SPSS and Amos were used for data analysis. Findings: The findings revealed the significant effects of all the direct and indirect effects and moderation was also accepted for the course availability and interactivity. Conclusion: This research examines the complex interplay between quality metrics, communication quality, and overall satisfaction among online learners to develop a deeper understanding of satisfaction in digital education. The study highlights the impact of three key quality factors on happiness in online learning contexts: interactivity, course accessibility, and learning preferences. It focuses on unraveling how these variables relate to and influence each other as well as learner contentment in virtual classrooms.